A Theoretical Foundation to Foster the University Education System in Sri Lanka: A Pragmatic Approach to Evacuate the Age-Old Gap - Ratnayake, B.R.M.N.; Kumara, K.H. Hemantha (My University, 2008)
Despite the fact that one pivotal role of the university education system in Sri Lanka is to fabricate proficient graduates as per the expectations by both private and public sector organizations meeting their competent criteria, we experience a situation of large number of graduates bear with unemployment. The recruiting issue of unemployment, underemployment and a variety of precaution taken by different authorities to resolve this crisis indicates that the current university system has not been able to cater to the needs of the society to a greater extent. Thus, the study focuses to formulate a mechanism to minimize the above crisis by suggesting a framework to reform the curriculum design. The objective of this study is to propose a theoretical framework for the university education where the expected knowledge, skills, and attitudes can be acquired by constructively aligning of the curriculum; learning outcomes, teaching learning activities and assessment addressing to three domains of learning; cognitive, affective and psychomotor. In each domain, the curriculum is designed assigning lower levels of taxonomy in the preliminary years of the degree program and progressively directing to higher levels of the degree program. Also within each level, objectives of learning, teaching methods , learning and assessment methods are constructively aligned. In conclusion, adoption of this theoretical framework to design the curriculum will be a milestone in the university system in Sri Lanka to evacuate the age-old gap and meet the industrial demand successfully.
Keywords: Unemployment; Curriculum; Constructive alignment; Taxonomy; Domains